Pengajaran Tuhan Yesus tentang Prinsip Melayani Anak Berdasarkan Markus 7:27-28 dan 9:35-42 - Matius I Totok Dwikoryanto (STIPAK Malang, 2021)
Many Christian families experience problems, the economy, unharmonious marriages, bad relationships, social media challenges, which result in children's spiritual formation often being prioritized to the church rather than the role of the family itself. Therefore, the church must be ready to be a place to prioritize teaching and child formation so that there is spiritual growth. From this, the education of children is important and the church must be able to form its mentality from childhood. By using a descriptive qualitative method and through a literature study approach to the text about the teaching of Jesus in the Gospel of Mark, it can be concluded that the teaching of the Lord Jesus must be carried out by providing maximum service to children's ministry, also paying attention to children's needs, and taking care of the physical child. The teaching of the Lord Jesus also gives meaning in the ethics of teaching faith. Even parents or the church must welcome children in every activity, especially preparing to be God's servants, this must be done as a priority for children.AbstractBanyaknya keluarga Kristen yang mengalami permasalahan, ekonomi, perkawinan yang tidak harmonis, pergaulan buruk, tantangan sosial media, yang berakibat pembinaan rohani anak seringkali diprioritas kepada gereja dari pada peran keluarga sendiri. Maka itu gereja harus siap menjadi tempat dalam memprioritaskan pengajaran dan pembentukan anak sehingga ada pertumbuhan rohani. Dari hal itu pendidikan kepada anak-anak merupakan hal yang penting dan gereja harus mampu membentuk mentalitasnya dari sejak anak-anak. Dengan menggunakan metode kualitatif deskriptif dan melalui pendekatan studi pustaka terhadap teks tentang pengajaran Yesus dalam Injil Markus, dengan demikian dapat disimpulkan pengajaran Tuhan Yesus harus dilaksanakan dengan memberikan pelayanan maksimal terhadap pelayanan Anak-anak, juga memperhatian terhadap kebutuhan anak, serta memeliharaan jasmani Anak. Pengajaran Tuhan Yesus juga memberikan makna dalam etika pengajaran Iman bahkan Orangtua atau gereja harus Menyambut Anak dalam setiap kegiatan terlebih mempersiapkan Menjadi Pelayan Tuhan hal itu harus dilakukan sebagai prioritas bagi anak.